A visible-light-driven photoelectrochemical molecularly imprinted sensor based on titanium dioxide nanotube arrays loaded with silver iodide nanoparticles for the sensitive detection of benzoyl peroxide. Issue 10 (17th April 2019) - Zhong, Li; Li, Xiuqi; Liu, Ruilin; Wei, Xiaoping; Li, Jianping
Abstract : A novel ultrasensitive photoelectrochemical sensor for benzoyl peroxide (BPO) was constructed under visible light irradiation. Abstract : A novel ultrasensitive photoelectrochemical sensor for benzoyl peroxide (BPO) was constructed under visible light irradiation. A novel nanostructured material made of molecularly imprinted polymer (MIP)-modified silver iodide nanoparticle–titanium dioxide nanotube arrays (AgINPs–TiO2 NTs) was designed as a photoactive electrode (denoted as MIP@AgINPs–TiO2 NTs). AgI-sensitized TiO2 nanotube arrays were prepared by a simple dissolution–precipitation–calcination process and then employed as a matrix to graft the MIP recognition element. Such a newly designed molecularly imprinted photoelectrochemical sensor exhibits high sensitivity and selectivity for the determination of BPO. The photoelectrochemical analysis is highly linear over the BPO concentration range from 1 × 10 −12 mol L −1 to 5 × 10 −10 mol L −1 with a detection limit of 2.53 × 10 −13 mol L −1 (S/N = 3, n = 11). The sensor designed based on a low cost and highly sensitive assay was successfully applied in the determination of BPO in spiked samples.